Opinion Article: Articular Cartilage: Lamellar-Repulsive Lubrication of Natural Joints by Zenon Pawlak - Kaldonski, Tadeusz (Edelweiss Applied Science and Technology, 2018)
This monograph attempts to explain a new joint lubrication mechanism with surface active phospholipids as a lubricant. It provides studies of the principles of cartilage (smart material) of biological micro- and Nano tribology